2018
DOI: 10.1177/2041731418811183
|View full text |Cite
|
Sign up to set email alerts
|

Tenogenically differentiated adipose-derived stem cells are effective in Achilles tendon repair in vivo

Abstract: The purpose of this study was to characterize rat adipose-derived stem cells, induce adipose-derived stem cell tenogenesis, and analyze adipose-derived stem cell effects on tendon repair in vivo. Adipose-derived stem cells demonstrated an immunomodulatory, pro-angiogenic, and pro-proliferatory profile in vitro. Tenogenesis was induced for 1, 7, 14, and 21 days with 24 combinations of growth differentiation factor-5, 6, and 7 and platelet-derived growth factor–BB. Adipose-derived stem cells expression of sclera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…During tissue repair, especially in bone, blood vessels supply not only oxygen and nutrients but also calcium and phosphate which are needed for mineralization [26]. us, for healing inflamed periapical lesions, the setting time of the materials applied in periapical lesion and consequent biological functions of MSCs during setting are important since the biological effects of the implanted materials in periapical lesions are contact time-dependent and extracts during setting influence MSCs' behaviors [9][10][11][12]. erefore, the effect of MTA against hMSCs was investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During tissue repair, especially in bone, blood vessels supply not only oxygen and nutrients but also calcium and phosphate which are needed for mineralization [26]. us, for healing inflamed periapical lesions, the setting time of the materials applied in periapical lesion and consequent biological functions of MSCs during setting are important since the biological effects of the implanted materials in periapical lesions are contact time-dependent and extracts during setting influence MSCs' behaviors [9][10][11][12]. erefore, the effect of MTA against hMSCs was investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…e setting time of the materials applied in periapical lesion of tooth and the consequent biological functions of MSCs during setting after implantation are important for the healing process of inflamed periapical lesions. Because the biological effects of the implanted materials are largely dependent on the contact time between materials and tissue, the ingredients and their amounts released from implant biomaterials give contact time dependent influence to MSCs' behaviors and biological functions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent study found that tenocyte induced tenogenic differentiation of BMSCs by secreting exosomes containing Tgf- β 1 [ 12 ]. BMP-induced tenogenic differentiation of AMSCs enhanced the expression of collagen type I and scleraxis and exhibited improved histological score and collagen fiber dispersion range compared to undifferentiated AMSCs [ 13 ]. Although the induction capacities were low, insulin-like growth factor 1 and basic fibroblast growth factor could still promote BMSCs to differentiate into tenocytes by upregulating collagen type I/III and scleraxis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent study found that tenocyte induced tenogenic differentiation of BMSCs by secreting exosomes containing Tgf-β1 [11]. BMP-induced tenogenic differentiation of AMSCs enhanced the expression of collagen type I and scleraxis and exhibited improved histological score and collagen fiber dispersion range compared to undifferentiated AMSCs [12]. Although the induction capacities were low, insulin-like growth factor 1 and basic fibroblast growth factor could still promote BMSCs to differentiate into tenocytes by upregulating collagen type I/III and scleraxis [13,14].…”
Section: Introductionmentioning
confidence: 99%